A simple corrosion fatigue design method for bridges considering the coupled corrosion-overloading effect. (1st January 2019) - Deng, Lu; Yan, Wangchen; Nie, Lei
Highlights: A simple corrosion fatigue design method for steel girder bridges is proposed. Effects of corrosion and overloading on reduction of fatigue life are investigated. Fatigue damage accumulation fashion under corrosion and overloading conditions is analyzed. Shear stress is more sensitive to corrosive environment as compared to bending stress. Abstract: Corrosion fatigue is more detrimental than either corrosion or overloading applied separately. Nevertheless, corrosion was not explicitly covered in the AASHTO LRFD fatigue design specifications, which may lead to underestimation of the fatigue damage of bridges. Moreover, simple approaches to evaluating the fatigue life of corroded steel components are still lacking. In this study, a steel girder bridge was adopted to study the coupled corrosion-overloading effect on the fatigue life of bridges. The variation of stress range, equivalent number of stress cycle, and the resulted cumulative fatigue damage under different corrosion and overloading conditions were investigated. Then, a simple corrosion fatigue design method was proposed by considering the coupled corrosion-overloading effect which covers the individual effects due to pure overloading, pure corrosion, and the corrosion-overloading interaction. The results showed that the relationship between the corrosion-overloading interaction and the corrosion depth can be well described by an exponential function which is applicable for different overloading and corrosion conditions. Moreover, the coupled corrosion-overloading effect can greatly reduce the fatigue life of bridges and should be carefully considered in bridge fatigue design wherever necessary.